Reaching for Precision Healthcare in Finland via Use of Genomic Data - Wahlfors, Tiina; Simell, Birgit; Kristiansson, Kati; Soini, Sirpa; Kilpi, Terhi; Erhola, Marina; Perola, Markus (Frontiers in Genetics, 2022)
Concerns over the future healthcare capacity along with continuing demands for sustainability forces developing novel solutions to improve citizens’ health and wellbeing through effective prevention and improved diagnosis and treatment. Part of the solution to tackle the challenge could be making the most of exploitation of genomic data in the personalized risk assessment, creating new opportunities for the data-driven precision prevention and public health. For the present, utilization of genomic data in the Finnish healthcare is limited to a few medical specialty areas. To successfully extend the use of genomic information in the everyday healthcare, evidence-based and feasible strategies are needed. The national actions that Finland is taking towards this goal are (1) providing scientific evidence for the utility of genomic information for the healthcare purposes; (2) evaluating the potential health-economic impact of implementing precision healthcare in Finland; and (3) developing a relevant legal framework and infrastructures for utilization of genomic information, (4) building a national multidisciplinary expert network bringing together relevant professionals and initiatives to achieve consensus among the different stakeholders on specific issues vital for translating genomic data into precision healthcare; (5) building competence and genomic literacy skills among various target groups. Taken together, these actions will enable building a roadmap towards expedient application of genomic data in the Finnish healthcare and promoting the health of our citizens.